Fibroblast Growth Factor 1 Reduces Pulmonary Vein and Atrium Arrhythmogenesis via Modification of Oxidative Stress and Sodium/Calcium Homeostasis - Lu, Yen-Yu; Cheng, Chen-Chuan; Huang, Shih-Yu; Chen, Yao-Chang; Kao, Yu-Hsun; Lin, Yung-Kuo; Higa, Satoshi; Chen, Shih-Ann; Chen, Yi-Jen (Frontiers in Cardiovascular Medicine, 2022)
Rationale: Atrial fibrillation is a critical health burden. Targeting calcium (Ca2+) dysregulation and oxidative stress are potential upstream therapeutic strategies. Fibroblast growth factor (FGF) 1 can modulate Ca2+ homeostasis and has antioxidant activity. The aim of this study was to investigate whether FGF1 has anti-arrhythmic potential through modulating Ca2+ homeostasis and antioxidant activity of pulmonary vein (PV) and left atrium (LA) myocytes. Methods: Patch clamp, western blotting, confocal microscopy, cellular and mitochondrial oxidative stress studies were performed in isolated rabbit PV and LA myocytes treated with or without FGF1 (1 and 10 ng/mL). Conventional microelectrodes were used to record electrical activity in isolated rabbit PV and LA tissue preparations with and without FGF1 (3 μg/kg, i.v.). Results: FGF1-treated rabbits had a slower heart rate than that observed in controls. PV and LA tissues in FGF1-treated rabbits had slower beating rates and longer action potential duration than those observed in controls. Isoproterenol (1 μM)-treated PV and LA tissues in the FGF1-treated rabbits showed less changes in the increased beating rate and a lower incidence of tachypacing (20 Hz)-induced burst firing than those observed in controls. FGF1 (10 ng/mL)-treated PV and LA myocytes had less oxidative stress and Ca2+ transient than those observed in controls. Compared to controls, FGF1 (10 ng/mL) decreased INa-L in PV myocytes and lowered Ito, IKr-tail in LA myocytes. Protein kinase C (PKC)ε inhibition abolished the effects of FGF1 on the ionic currents of LA and PV myocytes. Conclusion: FGF1 changes PV and LA electrophysiological characteristics possibly via modulating oxidative stress, Na+/Ca2+ homeostasis, and the PKCε pathway.